2018
DOI: 10.1111/imm.12958
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between invariant Natural Killer T cells and the mucosal microbiota

Abstract: SummaryThe surface of mammalian bodies is colonized by a multitude of microbial organisms, which under normal conditions support the host and are considered beneficial commensals. This requires, however, that the composition of the commensal microbiota is tightly controlled and regulated. The host immune system plays an important role in the maintenance of this microbiota composition. Here we focus on the contribution of one particular immune cell type, invariant Natural Killer T (iNKT) cells, in this process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 148 publications
(223 reference statements)
0
8
0
Order By: Relevance
“…iNKT cells recognise α-galactosylceramide (α-GalCer) and some similar lipid-derivatives such as microbial α-glycuronylceramides or human self-antigen isoglobotrihexosylceramide [3]. Moreover, they recognise various microbial antigens derived from microorganisms such as M. tuberculosis, B. burgdorferi, Aspergillus sp., and S. pneumoniae [4]. Type II NKT are activated by the CD1d-sulfatide complex, sulfatide is widely expressed in the kidney, liver, and central nervous system with sulfatide being one of the myelin sheath components [5,6].…”
Section: Nkt Cellsmentioning
confidence: 99%
“…iNKT cells recognise α-galactosylceramide (α-GalCer) and some similar lipid-derivatives such as microbial α-glycuronylceramides or human self-antigen isoglobotrihexosylceramide [3]. Moreover, they recognise various microbial antigens derived from microorganisms such as M. tuberculosis, B. burgdorferi, Aspergillus sp., and S. pneumoniae [4]. Type II NKT are activated by the CD1d-sulfatide complex, sulfatide is widely expressed in the kidney, liver, and central nervous system with sulfatide being one of the myelin sheath components [5,6].…”
Section: Nkt Cellsmentioning
confidence: 99%
“…All iNKT cells recognize and are potently activated by α-galactosylceramide (α-GalCer), a bacteria-derived glycolipid originally discovered in marine sponges [1]. Since then, several microbial antigens have been discovered both in pathogen and commensal microbes [7][8][9][10][11][12][13][14]. On the other hand, it has been demonstrated that the iNKT cell activation by self-antigens is important during thymic selection [1,15,16], infections [17][18][19][20], and autoimmune diseases [21].…”
Section: Inkt Cell Activationmentioning
confidence: 99%
“…This is achieved thanks to the capacity of iNKT cells to recognize microbial and microbe-induced self-antigens, as well as being activated by innate and cytokine signals, such as IL-12 and TLRs [50][51][52][53][54]. Given this, iNKT cells are important in the control of homeostasis in many mucosal tissues, like the intestine and lung, but also in the response against pathogens [9,[50][51][52][53][54][55][56]. More specifically, iNKT cells participate in the response against infectious agents mainly by mediating the activation of other immune cell types through the release of interferon (IFN) gamma [9,[50][51][52][53][54][55].…”
Section: Inkt Cell Cytotoxicity In Response To Infectionsmentioning
confidence: 99%
“…i NKT cells detect glycolipid Ags, including those derived from pathogens, presented within the hydrophobic pocket of CD1d [ 38 40 ] ( Fig 2A ). The antimicrobial properties of these invariant T ( i T) cells are owed to their tremendous immunomodulatory and cytolytic activities [ 32 , 41 43 ].…”
Section: Unmasking the Innate Face Of Immune Amnesiamentioning
confidence: 99%